Political theories for students - Miskelly, Matthew; Noce, Jaime (Gale virtual reference library, 2002)
In-depth information on major political theories and systems from all time periods. Each entry begins with a general overview of the system/theory followed by a discussion of the principal aspects of the theory, the theory's philosophy and an analysis of the historical context in which the theory was developed, including critical response.